Analysis of Textbook Needs for Educational Management and Policy Analysis Courses - Muhammad Kristiawan; Adelina Mariani S; Rambat Nur Sasongko; Erik Perdana Putra; Elsa Viona (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to see students’ responses regarding the need for textbooks for the Education Management and Policy Analysis Course in the Doctoral Education Study Program, FKIP, Universitas Bengkulu. This study was carried out by giving questionnaires to students to respond to their desired needs. This study was carried out through the Education Management and Policy Analysis Course. The results of this research showed that respondents needed a book for the Educational Management and Policy Analysis course and at the same time produced the Educational Management and Policy Analysis textbook. Research like this had been carried out before by other researchers, but with different topics and respondents, and the advantages of this study gave birth to the book Analysis of Educational Management and Policy. This study makes a contribution to the Doctor of Education Study Program regarding the addition of textbooks which also serve as references for the Education Management and Policy Analysis Course. The novelty of this study is the birth of a book for the Education Management and Policy Analysis Course. This study has implications for lecturers and students in the Doctor of Education Study Program who have a handbook on Education Management and Policy Analysis.